Media reforms in Myanmar and Indonesia: a critical analysis of how power relations and social inequalities are reflected in, impacted by, and shape media reform processes - S. Venkiteswaran, Gayathry (2025)
Southeast Asia has seen tremendous changes since the democratisation movements in the period of 1980s to the 1990s, in the Philippines, Thailand, and Indonesia. Political changes affect the media that experienced strict control and censorship, but at the same time, mobilised political changes in those countries. In the 2010s, a shift towards political openness began in Myanmar after decades of military rule. While these changes can be described as young or at a nascent stage, the other countries such as Indonesia, have seen remarkable developments in the area of media development and freedoms. Yet new challenges emerged even in the ‘success’ stories of democratization and press freedom. Key among them were the commercialisation of media, political divisions in society, and the rise of illiberal forces – a global phenomenon - that have pushed back some of the gains made in these societies. The opening in Myanmar that led to the election of a pro-democratic government in 2015, and lessons from Indonesia, inform this research on media reforms. Typically, with media reforms, come the negotiations between various domestic, regional, and international actors, vying control to direct the change process. Inspired by Monroe Price’s (2009) reflections of the media assistance project in Central and Eastern Europe in the 1990s, and Katrin Voltmer’s (2013) global analysis of media in transitional societies, I aim to analyse how different societies respond to, and shape media reforms, who sets the agendas for reforms and what these mean to the different actors. Central to the discussion is the role of the various elements of the state and authority that are ‘fragmented and contentious’, as proposed by Migdal (2001), in its interaction with other fields of power to such as capital and international development, which dominate the reforms process and outcomes, and the public. The thesis critically engages with theories of participation and gender in the context of democracy and development to interrogate the relationships between the actors and what lessons can be learnt from the experiences in the two countries.